A dopamine metabolite stabilizes neurotoxic amyloid-β oligomers - Rodrigo Cataldi (Nature Portfolio, 2021)
Cataldi et al. investigates the impact of the dopamine derivative DOPAL on the Aβ peptide oligomer formation. They report that DOPAL promotes the formation of stable Aβ oligomers that exert toxicity on neuroblastoma cells by increasing cytosolic calcium levels and generating reactive oxygen species. This study connects Aβ aggregation with processes regulating cellular homeostasis in the brain.